Structural and Optical Properties of (MgZnO/rGO) Nanocomposites - Gunja Lavanya; Thirukachhi Suvarna; C.P. Vardhani (Journal of Chemistry Letters)
Magnesium-Zinc oxide/Reduced Graphene Oxide (MgZnO/rGO) nanocomposites have been successfully synthesized by the Co-precipitation process .Obtained materials were characterized by the X-ray diffraction (XRD) shows both the hexagonal wurtzite structure of ZnO crystal planes and cubic structure of MgO. This fact shows that the prepared samples are not a single phase but a composite. Peak broadening indicates that the smaller crystallites size of the prepared MgZnO/rGO nanocomposites .The structural morphology was studied by Field emission Scanning electron microscope (FESEM) shows that the nanoparticles are connected with each other to form agglomerated granular structure which may be due to the high surface to volume ratio that results in high surface energy and the elemental analysis is confirmed by Energy dispersive X-ray analysis (EDAX) shows four strong peaks correspond to carbon (C), oxygen (O), zinc (Zn) and magnesium(Mg) with different weight percentages by doping Mg at different compositions. The functional groups of the samples are confirmed by the Fourier-transform infrared spectroscopy (FTIR) observed in the spectra at nearly ~3685 due to the O-H Stretching vibrations, peaks observed at ~2860 due to the C-H stretching vibrations,1596-1545 due to the C=O stretching vibrations. The strong bands located at 746 and 530 cm−1 indicate the stretching vibration mode of Mg–O and Zn–O, respectively, which confirm the formation of MgZnO/rGO nano composites. The optical properties of the prepared MgZnO/rGO samples are characterized by the UV-visible absorption to determine the band gap of the metal oxide nanocomposites. It can be seen in all the spectra that the strong absorption peaks were appeared at around 350 nm, which is attributed to the band gap absorption in MgZnO nanocomposites. The calculated values of the band gap energies of MgZnO nanocomposites are 3.47, 3.48 and 3.51eV respectively, at wavelengths 357nm, 356nm and 352nm which are good agreement with reported band gap values of MgZnO nanocomposites. Most studies have been concentrated on thin films; synthesis and study of MgZnO nanocomposites are rare. MgZnO/rGO nanocomposites are mainly applicable in various electrical, optoelectronic and photo catalytic applications. In the present study, Mg-doped ZnO/rGO with different Mg compositions was prepared by Co-precipitation method with subsequent calcination at high temperature .Crystalline structure, morphology and optical properties were investigated and discussed according to the experimental results.